THE ROLE OF THE MEDIA IN THE IMPLEMENTATION OF PUBLIC CONTROL - Umarov Murodjon Mamatkarim ugli, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses how massively the media operating in the Republic of Uzbekistan add to the implementation of public control and the openness of their activities, as well as their interaction with state authorities and governing bodies.